Micropoetry Meets Neurocognitive Poetics: Influence of Associations on the Reception of Poetry - Hugentobler, Katharina Gloria; Lüdtke, Jana (Frontiers in Psychology, 2021)
Reading and understanding poetic texts is often described as an interactive process influenced by the words and phrases building the poems and all associations and images induced by them in the readers mind. Iser, for example, described the understanding process as the closing of a Good Gestalt promoted by mental images. Here we investigate the effect that semantic cohesion, that is the internal connection of a list words, has on understanding and appreciation of poetic texts. To do this word lists are presented as modern micropoems to the participants and the (ease of) extraction of underlying concepts as well as the affective and aesthetic responses are implicitly and explicitly measured. We found that a unifying concept is found more easily and unifying concepts vary significantly less between participants when the words composing a micropoem are semantically related. Moreover these items are liked better and are understood more easily. Our study shows evidence for the assumed relationship between building spontaneous associations, forming mental imagery, and understanding and appreciation of poetic texts. In addition, we introduced a new method well suited to manipulate backgrounding features independently of foregrounding features which allows to disentangle the effects of both on poetry reception.